2019
DOI: 10.1038/s41598-019-48059-7
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in lipid metabolism of spinal cord linked to amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is characterized by progressive loss of upper and lower motor neurons leading to muscle paralysis and death. While a link between dysregulated lipid metabolism and ALS has been proposed, lipidome alterations involved in disease progression are still understudied. Using a rodent model of ALS overexpressing mutant human Cu/Zn-superoxide dismutase gene (SOD1-G93A), we performed a comparative lipidomic analysis in motor cortex and spinal cord tissues of SOD1-G93A and WT rats at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
102
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 114 publications
(126 citation statements)
references
References 69 publications
8
102
0
Order By: Relevance
“…LD accumulation has been observed in glial cells, including astrocytes, in early stages of neurodegeneration 46 . Recently, alterations in lipid metabolism (accumulation of cholesteryl esters, determined with lipidomic analysis) in spinal cords from SOD1 G93A transgenic mouse model have been reported that might be linked to astrogliosis and LD formation in astrocytes 48 , since a population of astrocytes isolated from the degenerating spinal cords of the same animal model exhibited significant abundance of LDs as well as autophagic and secretory vesicles, all characteristic features of cellular stress and inflammatory activation 70 . However, the mechanisms leading to increased LD accumulation in astrocytes are poorly understood and may, among others, rely on altered neuronal mitochondrial function and ROS as well as on astrocyte-neuron lactate shuttle 47 , in particular on astroglial lactate-derived lipid production in neurons and transfer of excess lipids in lipoprotein-like particles (ApoE) from neurons to astrocytes 47,71 .…”
Section: Discussionmentioning
confidence: 99%
“…LD accumulation has been observed in glial cells, including astrocytes, in early stages of neurodegeneration 46 . Recently, alterations in lipid metabolism (accumulation of cholesteryl esters, determined with lipidomic analysis) in spinal cords from SOD1 G93A transgenic mouse model have been reported that might be linked to astrogliosis and LD formation in astrocytes 48 , since a population of astrocytes isolated from the degenerating spinal cords of the same animal model exhibited significant abundance of LDs as well as autophagic and secretory vesicles, all characteristic features of cellular stress and inflammatory activation 70 . However, the mechanisms leading to increased LD accumulation in astrocytes are poorly understood and may, among others, rely on altered neuronal mitochondrial function and ROS as well as on astrocyte-neuron lactate shuttle 47 , in particular on astroglial lactate-derived lipid production in neurons and transfer of excess lipids in lipoprotein-like particles (ApoE) from neurons to astrocytes 47,71 .…”
Section: Discussionmentioning
confidence: 99%
“…31 Altered sphingolipids included sphingomyelins, sphingosines, ceramides and hexosylceramides, which have been previously reported in ALS participant plasma, 14 15 25 CSF, 8 and spinal cord, 32 33 and ALS mouse models. [32][33][34][35] Targeting sphingolipid metabolism with sphingolipid inhibitors is at the forefront of cancer therapeutics, 36 and has been advocated as a possible treatment for Alzheimer's, Parkinson's and Huntington's disease. 37 38 Our study provides evidence that sphingolipid metabolism may similarly be targeted in ALS as a potential therapeutic opportunity.…”
Section: Figurementioning
confidence: 99%
“…This homogenate was mixed with 400 μL of ice-cold methanol, containing 100 μM of butylated hydroxytoluene (BHT), and 100 μL of internal standards (10 µg/mL). 2 mL of chloroform: ethyl acetate (4:1) were added to the mixture, followed by vortexing during 30 s. After centrifugation at 1,500 x g for 2 min at 4°C, the lower phase containing total lipid extracts (TLE) was transferred to a new tube and dried under N 2 gas 63 . Dried TLE were dissolved in 100 µL of isopropanol and the UHPLC injection volume was set at 2 µL.…”
Section: Methodsmentioning
confidence: 99%